Acute and Chronic Injury Patterns in Competitive Paraclimbing Sports - von Essen, Daniel; Schöffl, Volker Rainer (American Journal of Physical Medicine & Rehabilitation, 2023)
Objective This is the first study to evaluate sport-related injuries in competitive Paraclimbing athletes with the aim of creating a medical database for future research on injury prevention. Design This was a descriptive epidemiology study. Data collection took place in two parts. In the first part, an online survey (n = 81) was conducted. The second part was undertaken during three competitions (n = 273) of the 2021 International Federation of Sport Climbing Paraclimbing competitions. Injury severity grading was determined using the Climbing Injury Score of the International Federation of Sport Climbing. Results In the online survey, 76 injuries were reported: 62% acute and 38% chronic injuries. Injury severity was as follows: 21 scored 1, 34 scored 2a, 19 scored 2b, and 2 scored 3. The most injured body regions were the upper extremity (66%) with shoulder injuries (29%) most common; 53% reported regular pain/discomfort during training/competition and 16% used nonsteroidal anti-inflammatory drugs regularly to prevent pain/discomfort when training. In the 2021 International Federation of Sport Climbing Paraclimbing competitions, eight injuries were recorded. Injury severity was as follows: seven scored 1 and one scored 2a. The most injured body region was the upper extremity (47%). Overall, the calculated climbing time was 975 hrs, and injury incidence risk was 8.21 per 1000 hrs. Conclusion Compared with nondisabled climbers, the injury pattern seems to be sport dependent but influenced by the unique impairments of the athletes. In Paraclimbing competitions, the injury severity is mostly mild, with an overall low injury incidence. A concern is the number of athletes with pain/discomfort during training/competition with regular nonsteroidal anti-inflammatory drug intake.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Injury Surveillance; Mountaineering/Rock Climbing; Paraclimbing; Parasport